Comparison of the effects of inhaled ipratropium bromide and salbutamol on the bronchoconstrictor response to hypocapnic hyperventilation in normal subjects. - Jamison, J P (1987)
A double blind, placebo controlled comparison was made of the effects of nebulised ipratropium bromide (0.05 and 0.5 mg) and salbutamol (0.25 and 2.5 mg) on lung function and the airway response to hyperventilation in eight normal subjects. Both agents at both doses caused similar baseline bronchodilatation, confirming the presence of resting bronchomotor tone. The overall mean increases as percentages of control were 33% in specific airway conductance (sGaw), 10% in maximal flow after expiration of 50% of vital capacity, and 3.7% in FEV1. Hypocapnia (mean end tidal carbon dioxide tension 2.2 kPa) was produced by three minutes of voluntary hyperventilation and resulted in a mean fall in sGaw of 0.49 s-1 kPa-1 (20%). After inhalation of 0.25 mg salbutamol hypocapnic hyperventilation still produced a mean fall in sGaw of 0.55 s-1 kPa-1, whereas salbutamol 2.5 mg reduced this response to 0.15 s-1 kPa-1 (6%). After both doses of ipratropium the decrease in sGaw caused by hyperventilation was similar to the control. This suggests that bronchoconstriction in response to hypocapnic hyperventilation in normal subjects is not mediated via a cholinergic reflex.